Functional Adaptation of LPS‐affected Dentoalveolar Fibrous Joints in Rats. (28th November 2021) - Wang, Bo; Ustriyana, Putu; Tam, Caleb. S.; Lin, Jeremy. D.; Srirangapatanam, Sudarshan; Kapila, Yvonne; Ryder, Mark I.; Webb, Samuel; Seo, Youngho; Ho, Sunita. P.
Abstract: Introduction: The functional interplay between cementum of the root and alveolar bone of the socket is tuned by a uniquely positioned 70–80 µm wide fibrous and lubricious ligament in a dentoalveolar joint (DAJ). In this study, structural and biomechanical properties of the DAJ, periodontal ligament space (PDL‐space also known as the joint space), alveolar bone of the socket, and cementum of the tooth root that govern the biomechanics of a lipopolysaccharide (LPS)‐affected DAJ were mapped both in space and time. Methods: The hemi‐maxillae from 20 rats (4 control at 6 weeks of age, 4 control and 4 LPS‐affected at 12 weeks of age, 4 control and 4 LPS‐affected at 16 weeks of age) were investigated using a hybrid technique; micro‐X‐ray computed tomography (5 µm resolution) in combination with biomechanical testing in situ . Temporal variations in bone and cementum volume fractions were evaluated. Trends in mineral apposition rates (MAR) in additional six Sprague Dawley rats (3 controls, 3 LPS‐affected) were revealed by transforming spatial fluorochrome signals to functional growth rates (linearity factor ‐ RW) of bone, dentin, and cementum using a fast Fourier transform on fluorochrome signals from 100‐µm hemi‐maxillae sections. Results: An overall change in LPS‐affected DAJ biomechanics (a 2.5–4.5X increase in tooth displacement and 2X tooth rotation at 6 weeks, no increase in displacement and a 7X increase in rotation at 12 weeks; 27% increase in bone effective strain at 6 weeks and 11% at 12 weeks relative to control) was associated with structural changes in the coronal regions of the DAJ (15% increase in PDL‐space from 0 to 6 weeks but only 5% from 6 to 12 weeks compared to control). A significant increase ( p < 0.05) in PDL‐space between ligated and age‐matched control was observed. The bone fraction of ligated at 12 weeks was significantly lower than its age‐matched control, and no significant differences ( p > 0.05) between groups were observed at 6 weeks. Cementum in the apical regions grew faster but nonlinearly (11% and 20% increase in cementum fraction (CF) at 6 and 12 weeks) compared to control. Alveolar bone revealed site‐specific nonlinear growth with an overall increase in MAR (108.5 µm/week to 126.7 µm/week after LPS treatment) compared to dentin (28.3 µm/week in control vs. 26.1 µm/week in LPS‐affected) and cementum (126.5 µm/week in control vs. 119.9 µm/week in LPS‐affected). A significant increase in CF ( p < 0.05) in ligated specimens was observed at 6 weeks of age. Conclusions: Anatomy‐specific responses of cementum and bone to the mechano‐chemo stimuli, and their collective temporal contribution to observed changes in PDL‐space were perpetuated by altered tooth movement. Data highlight the "resilience" of DAJ function through the predominance of nonlinear growth response of cementum, changes in PDL‐space, and bone architecture. Despite the significant differences in bone and cementum architectures, data provided insights into the reactionary effects of cementum as a built‐in compensatory mechanism to reestablish functional competence of the DAJ. The spatial shifts in architectures of alveolar bone and cementum, and consequently ligament space, highlight adaptations farther away from the site of insult, which also is another novel insight from this study. These adaptations when correlated within the context of joint function (biomechanics) illustrate that they are indeed necessary to sustain DAJ function albeit being pathological.